PREGNANCY IN PATIENTS ANTICOAGULATED WITH WARFARIN SODIUM - Razzeto Ríos, Luis (2015)
From January 1980 to December 1986 we carried out the study of seven pregnancies in six patients anticoagulants (Warfarin Sodium) who suffered mechanical valve replacement between January 1980 and December 1986 was conducted: to determine the risk of the mother and fetus by the use of coumarin throughout pregnancy . He was considered: the start of treatment, Gynecology and obstetrics prior history, duration of treatment, drugs used, adequate control and termination of pregnancy, as well as monitoring newborns. Two spontaneous abortions (28.57%) presented; fetal death (14.28%), the birth of 2 children and 2 with congenital anomalies in pregnancies more current developments. In all pregnancies she is presented ginecorragia, increasing the risk of Abortion by 100%. Associations of anticoagulant therapy during pregnancy with congenital anomalies, demonstrating their tetratógenos effects. It is the first case reported worldwide Chondrodysplasia Puncrata and situs inversus totalis associated with the use of Warfarin Sodium, during pregnancy.